Comparative study of preterm infants fed new and existing human milk fortifiers showed favourable markers of gastrointestinal status. (30th September 2019) - Rigo, Jacques; Hascoët, Jean‐Michel; Picaud, Jean-Charles; Mosca, Fabio; Rubio, Amandine; Saliba, Elie; Radkë, Michaël; Simeoni, Umberto; Guillois, Bernard; Hays, Nicholas P.; Hartweg, Mickaël; Billeaud, Claude; et al.
Abstract: Aim: This study examined the influence of different human milk fortifiers on biomarkers of gastrointestinal immaturity and inflammation in preterm infants. Methods: We report secondary outcomes from a controlled, double‐blind, randomised, parallel group study conducted from 2011 to 2014 in neonatal intensive care units at 11 metropolitan hospitals in France, Belgium, Germany, Switzerland and Italy. Preterm infants born at up to 32 weeks or weighing up to 1500 g were randomised to a new powdered human milk fortifier (n = 77) or a control fortifier (n = 76) for a minimum of 21 days. We analysed faecal markers of gut inflammation, namely alpha‐1 antitrypsin and calprotectin, and maturity, namely elastase‐1. Results: Faecal alpha‐1 antitrypsin was slightly lower in the new than control fortifier group after 21 days of full enteral feeding, with a geometric mean and standard deviation of 1.52 ± 1.32 vs 1.82 ± 1.44 mg/g stools ( P = .01). There was no significant difference in faecal calprotectin (median [Q1‐Q3] of 296 [136‐565] μg/g stools in both groups combined at study day 21). Faecal elastase‐1 was lower in the new fortifier than control fortifier group (202.5 ± 1.6 vs 257.7 ± 1.5 μg/g stools, P = .016). Conclusion: Mean values for each parameter were within the ranges in healthy term infants, indicating favourable markers of gastrointestinal status in both groups. In addition, for faecal calprotectin, the relatively high concentration observed in preterm infants fed fortified human milk suggests that the threshold level for detecting necrotising enterocolitis should be revised.